Cemented backfilling performance of yellow phosphorus slag - Chen, Jia-sheng; Zhao, Bin; Wang, Xin-min; Zhang, Qin-li; Wang, Li (International journal of minerals, metallurgy and materials, 2010)
The experiments on the cemented backfilling perfbrmance of yellow phosphorus slag, including physical-mechanical properties, chemical compositions, optimized proportion, and cementation mechanisms, were carried out to make good use of yellow phosphorus slag as well as tackle with environment problems, safety problems, geological hazards, and high-cost issues during mining in Kaiyang Phosphorus Mine Group, Guizhou. The results show that yellow phosphorus slag can be used as the cement substitute for potential coagulation property. Quicklime, hydrated lime, and other alkaline substances can eliminate the high residual phosphorus to improve the initial strength of backfilling body. The recommended proportions （mass ratio） are 1：1 （yellow phosphorus slag：phosphorous gypsum）, 1：4：10 （Portland cement：yellow phosphorus slag：phosphorous gypsum）, and 1：4：10 （ultra fine powder：yellow phosphorus slag：phosphorous gypsum） with 5wt% of hydrated lime addition, 60wt% of solid materials, no fly ash addition, and good rheological properties. The hydration reaction involves hydration stage, solidifying stage, and strength stage with Ca（OH）2 as the activating agent. The reaction rates of yellow phosphorus slag, Portland cement, and ultrafine powder hydration with the increase of microstructure stability and initial strength.